The impact of digital economy and industrial structure distortion on Xinjiang’s energy intensity under the goal of “double carbon” - Guo, Qingran; Ding, Cuicui; Wu, Zhuo; Guo, Bocheng; Xue, Yongxuan; Li, Depeng (Frontiers in Environmental Science, 2022)
Reducing energy intensity is an important measure to achieve the goal of “double carbon” and build a beautiful Xinjiang. Selecting the panel data of 14 regions in Xinjiang from 2010 to 2020, this paper investigates the influence of digital economy and industrial structure distortion on Xinjiang's energy intensity. The results show that the digital economy can reduce the energy intensity, but it has regional heterogeneity, and its inhibitory effect on northern Xinjiang is significantly higher than that in southern Xinjiang. The industrial structure distortion has significantly improved Xinjiang's energy intensity; Digital economy effectively alleviates the industrial structure distortion, thus curbing energy intensity; The influence of digital economy on Xinjiang's energy intensity has intermediary effect and adjustment effect, and with the improvement of industrial structure distortion, the inhibitory effect of digital economy on Xinjiang's energy intensity tends to decline. Therefore, it is necessary to speed up the development of digital economy, reduce the industrial structure distortion, strengthen environmental regulation, promote technological innovation, rationally adjust energy prices, raise the entry threshold of FDI, expand opening to the outside world, promote the synchronous scientific development of “four modernizations”, and eliminate the root causes of industrial structure distortion, so as to reduce energy intensity.